Archaeological excavation in tell Lashkir: 2022 fieldwork season - Aziz Muhamadamin Zebari; Abdullah Bakr Othman; Hawkar Ahmed Abdullrahman; Nader Babaker; Miquel Molist (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Archaeological excavation is a scientific practice carried out by archaeologists to reveal the remains of ancient humans. The archaeological excavations at Tell Lashkar dates back to 2015 by the archaeological team of the Autonomous University of Barcelona, the Department of Archeology of Salahaddin University and the Erbil Archaeological Directorate. Excavation work continued from 2015 to 2018, then stopped in 2019-2020 due to the coronavirus pandemic and continued again from 2021 to now. The excavations continued for seven seasons and revealed many important archaeological remains that provide important information about the history of the region and the civilization of Kurdistan and ancient Iraq. In this study, which is a joint excavation of the three themes mentioned earlier, the archaeological excavation of the 2022 season at Tell Lashkar will be included. Researchers have tried to present all the remains found through data and show complete information, and in our research, we will discuss the remains found such as architecture, pottery, graves, cosmetics, Kiln, Fire installation and other remains.